Recombinant growth hormone therapy in children with short stature in Abu Dhabi: a cross-sectional study of indications and treatment outcomes - Al Jneibi, Sara Salem; Taha, Fatima; Hammouri, Marwa; Allami, Zahraa; Weber, Stefan; Aljubeh, Jamal; Al Remeithi, Sareea (Frontiers in Pediatrics, 2025)
Early diagnosis of the pathological cause, if any, of short stature in children can lead to prompt intervention with recombinant growth hormone (rGH) treatment, potentially allowing them to achieve their true genetic height potential. However, it is crucial to identify children most likely to benefit from rGH treatment.MethodsThis cross-sectional, retrospective study provides a broad overview of rGH prescribing patterns and evaluates both short- and long-term treatment outcomes in children treated at the Pediatric Endocrinology Clinic, Sheikh Khalifa Medical City, Abu Dhabi, UAE, between January 2011 and December 2022. One- and three-year outcome data for children treated with rGH for different diagnoses of short stature were assessed.ResultsIdiopathic short stature (ISS) accounted for 34.8% of the cases for which rGH was prescribed. A significant response [mean height gain of ≥0.3 standard deviation score (SDS)/year] was seen across all assessed short-stature diagnoses, with the highest gain seen in the growth hormone deficiency (GHD) diagnosis group at the 1-year and 3-year treatment time points. More than 90% of the children diagnosed with GHD and ISS achieved normal final adult height. Younger age at rGH initiation, lower height SDS at baseline, and pre-pubertal status were associated with better outcomes post 1 and 3 years of rGH therapy. Greater response at 1 year of rGH therapy was associated with better final adult height outcome.ConclusionsISS was the most common indication for which rGH was prescribed in this study. A favorable increment in the height SDS of the rGH-treated children during their 1- and 3-year follow-ups was observed. Age, pubertal status, baseline height SDS, and rGH response at 1 year were directly associated with significantly improved short- and long-term response to rGH treatment. These findings provide a broad overview of the baseline and therapeutic response characteristics of rGH-treated children with short stature in the UAE and can help in optimizing and personalizing treatment strategies.